Exploring junior high school students' critical thinking skills in physics learning problem solving: evidence from work and energy - Lubis, Nur Azizah; Erlangga, Sony Yunior; Yektyastuti, Resty (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study examines to identify and compare the stages of students reasoning during the learning process, and to understand the role of teacher facilitator in shaping students critical thinking development. The research was conducted using a qualitative descriptive approach through observations, interviews, and document analysis. Data were coded following the Saldana model to generate categories and themes of students reasoning. The findings indivate a gradual development of students thinking. In the early cycle, students mainly focused on identifying problems and making simple interpretations, while in the following cycle they began to demonstrate analysis, evaluation, and more structured conclusions. Teacher facilitation and group collaboration were found to play an important role in supporting this process. Overall, the study highlights that problem solving based physics learning fosters the growth of comprehensive reasoning abilities and strengthens students learning independence. These results contribute to the improvement of instructional practices that emphasize higher order competencies needed in the 21st century.